Pilihan Rasional Mahasiswa Difabel dalam Memilih Jurusan Keguruan - Ferdinan Bashofi; Winin Maulidya Saffanah (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The existence of a supportive environment is very important for a person with disabilities in deciding things include of choosing school to continue their education. This study intends to look at rational reasons and choices for disabled students who take the teaching profession. The researcher intends to highlight a number of factors that encourage these students on choosing the teaching profession. The choice of students with disabilities is very important to study because it can be a study material for their reasons for studying and for the development of a friendly campus for disabled people in the future. This study use qualitative descriptive research design. The research data was obtained from interviews conducted with a number of selected informants. In addition to interviews, data collected by observing their behavior. To maintain data validity, data triangulation is carried out. Data analysis activities begin with data collection, data reduction, and data presentation. One findings of people with disabilities taking educational study programs is motivated to encouraged people with the same conditions. On the other hands, the teaching profession is also not as physically demanding as other professions and feel like a reasonable choice.